Cell immobilization technique for biotrickle filtering of isopropyl alcohol waste vapor generated by high‐technology industries. Issue 3 (10th May 2012) - Tsai, Shen‐Long; Lin, Chi‐Wen; Wu, Chih‐Hung; Xin, Baoping
Abstract BACKGROUND: A bench‐scale biotrickling filter coupled with Pseudomonas citronellolis YAIP521‐immobilized polyvinyl alcohol (PVA)/alginate beads was developed for kinetic analysis of microbial removal of isopropyl alcohol (IPA), an organic solvent widely used for fabricating wafers and printed circuit boards. RESULTS: Response surface methodology (RSM) showed that the optimal ratio of PVA to alginate was 7.5 g to 0.8 g. More than 95% of IPA removal could be achieved at an inlet concentration of 220 ± 34 ppm (w/w) under short residency time. System stability decreased under high IPA concentration and intermittent shock‐loading conditions but increased when using cell‐immobilized beads because the buffer effect limited the adverse impacts of high IPA concentrations on microorganisms, and the system gradually stabilized with IPA removal efficiency as high as 95%. Nevertheless, qPCR indicated that intermittent shock‐loading decreased the biomass in the beads. CONCLUSION: The experimental results showed that the biotrickling filter system developed effectively diminishes the inhibitory effects of elevated IPA concentration on microbial growth, thereby solving the problem of high IPA loading often encountered in the electronic high‐tech industries. The design of the system along with the population dynamics and reaction kinetics provide superior information to ensure the success of the biotrickling filter system. © 2012 Society of Chemical Industry